Desain Antarmuka Rekam Medis Elektronik Berbasis Android Untuk Mendukung Kesiapsiagaan Bencana Di Puskesmas Berambai Kabupaten Barito Kuala - Hastin Atas Asih; Soraya Soraya; Ahmad Rasyid R.R; Bella Mardya; Bagus Dwi Purwanto; Alvina Ahsana Nadilla (Akademi Keperawatan Yarsi Samarinda, 2026)
Background: Indonesia is prone to natural disasters, such as floods that frequently hit Barito Kuala Regency. Fast and accurate access to medical record data is crucial in emergency response, yet conventional paper-based systems are vulnerable to damage and difficult to access. Android-based Electronic Medical Record (EMR) technology offers a potential solution to enhance disaster preparedness in primary health facilities such as Community Health Centers (Puskesmas). Objective: This study aims to design and evaluate user perceptions of the interface design for an Android-based EMR application designed to support disaster preparedness at Berambai Community Health Center, Barito Kuala Regency. Methods: The study used a descriptive quantitative method. A total of 26 health workers and employees of Berambai Community Health Center were respondents through a questionnaire adopted from previous research. Data were analyzed univariately to describe respondent characteristics and their perceptions of the proposed interface design. Results: The majority of respondents (92.3%) perceived the system positively in terms of ease of use during disaster simulation. About 92.4% agreed the system could be learned quickly, and 96.2% stated that disaster-related features (triage, evacuation history) were well integrated. However, 46.2% of respondents still perceived complexity under pressure, and 88.5% stated the need for initial learning or training before full operation. Conclusion: The Android-based EMR interface design is generally well received and considered potential to improve health data access in disaster situations. Successful implementation requires technical assistance, structured training, and continuous design refinement to ensure optimal usability in real emergency conditions.